Bildung in the Era of Digital Media - Taekke, Jesper; Paulsen, Michael Eric (Journal of Sociocybernetics, 2016)
We are living in a period where new social structures arise in the communicative space and wake of digital media. This means that we must try to adapt to a changing social world within all social arenas like economy, work-life, love relations and last but not least education. The question of this paper is what Bildung should be or could be within this new medium environment. It draws on Luhmann (2006), Biesta (2006), Klafki (2014) and Kant (1784) describing what Bildung is seen from the view of the enlightenment tradition and try to discuss and analyze how ideas of Bildung could be used in education today and tomorrow. The paper draws on empirical findings from the Socio Media Education experiment, a Danish action research project in an upper secondary school from 2011-214 (XXXX 2013a, 2015a, 2016a, 2016b).